Trabalho e Autonomia: entre as atribuições e caminhos do exercício do supervisor de ensino - RIBEIRO, Elidia Vicentina de Jesus (2018)
The present research aims to analyze how the categories work autonomy in the development of the atribuitions of the superviser of the teaching in the state network São Paulo. As a research focus, we chose to conceptualize the term work, based on the theoretical foundations of Marx, and the term autonomy, presenting it initially as a polysemic concept and then emphasizing the analysis from the relation with the conceptions of Adorno and Horkheimer on emancipation. As specific objectives, the research sought to characterize the teaching supervisor, with a historical survey of the supervisor's performance, situating it in relation to the constitution of the position and identifying the existing relationships with the functions currently exercised by the supervisor of teaching, besides situá them within the structure of the State Secretariat of Education of the State of São Paulo. The methodology used is composed of bibliographical research on the themes of work and autonomy, a historical survey on teaching supervision in the State of São Paulo and the attributions of the position and its current characterization, documentary research from the legislation that concerns the functions of supervision of teaching, research through questionnaire application to the teaching supervisors of the Teaching Board of Itapetininga and interview with the Regional Director of the same Teaching Board about the work of the teaching supervisor. The data collected in the application of the questionnaires form and semi-structured interview were articulated with the bibliography researched, in order to seek a conclusion to respond the scope of the present study. The main results obtained refer to the analysis of the conceptions about autonomy that are present in the understanding of the professionals researched and how these relate to the possible paths of supervision of teaching, going beyond the limits of alienated work, aiming at the conquest of actions that represent the work and emancipation.